Structural change as a key component for agricultural non-CO2 mitigation efforts - Frank, Stefan; Beach, Robert H.; Havlík, Petr; Valin, Hugo; Herrero, Mario; Mosnier, Aline; Hasegawa, Tomoko; Creason, Jared; Ragnauth, Shaun; Obersteiner, Michael (Springer, 2018)
Agriculture is the single largest source of anthropogenic non-carbon dioxide (non-CO2) emissions. Reaching the climate target of the Paris Agreement will require significant emission reductions across sectors by 2030 and continued efforts thereafter. Here we show that the economic potential of non-CO2 emissions reductions from agriculture is up to four times as high as previously estimated. In fact, we find that agriculture could achieve already at a carbon price of 25 $/tCO2eq non-CO2 reductions of around 1 GtCO2eq/year by 2030 mainly through the adoption of technical and structural mitigation options. At 100 $/tCO2eq agriculture could even provide non-CO2 reductions of 2.6 GtCO2eq/year in 2050 including demand side efforts. Immediate action to favor the widespread adoption of technical options in developed countries together with productivity increases through structural changes in developing countries is needed to move agriculture on track with a 2 °C climate stabilization pathway.